2013
DOI: 10.1242/jcs.123042
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Trafficking of STAT5 Depends on an Unconventional Nuclear Localization Signal

Abstract: SummarySignal transducer and activator of transcription 5 (STAT5) is crucial for physiological processes that include hematopoiesis, liver metabolism and mammary gland development. However, aberrant continual activity of STAT5 has been causally linked to human leukemias and solid tumor formation. As a regulated transcription factor, precise cellular localization of STAT5 is essential. Conventional nuclear localization signals consist of short stretches of basic amino acids. In this study, we provide evidence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 79 publications
(108 reference statements)
1
28
0
Order By: Relevance
“…Live cell imaging with cytoplasmic FLIP was used to follow the kinetics of STAT5A-GFP nuclear export in the presence or absence of the Crm1 inhibitor LMB. 97 LMB was found to reduce the kinetics of STAT5A nuclear export, but it did not eliminate its nuclear export. Analysis of fragments of STAT5A capable of mediating nuclear export identified a Crm1-dependent NES in STAT5A N-terminus, and a Crm1-independent NES within the DBD of STAT5A.…”
Section: Stat5mentioning
confidence: 86%
See 3 more Smart Citations
“…Live cell imaging with cytoplasmic FLIP was used to follow the kinetics of STAT5A-GFP nuclear export in the presence or absence of the Crm1 inhibitor LMB. 97 LMB was found to reduce the kinetics of STAT5A nuclear export, but it did not eliminate its nuclear export. Analysis of fragments of STAT5A capable of mediating nuclear export identified a Crm1-dependent NES in STAT5A N-terminus, and a Crm1-independent NES within the DBD of STAT5A.…”
Section: Stat5mentioning
confidence: 86%
“…97 The coiled-coil domain of STAT5 is composed of four α-helices. 93 Evaluation of each of these helices tagged with GFP either alone or in combination demonstrated that all four α-helices were required for effective nuclear import.…”
Section: Stat5mentioning
confidence: 99%
See 2 more Smart Citations
“…In support of this idea, ectopic STAT3 activity in vitro can promote AT2 differentiation in the absence of exogenous Dx. Interestingly, GR and STAT proteins have been reported to act together in multiple settings via several molecular mechanisms including joint transcriptional activation and/or repression (Engblom et al, 2007; Langlais et al, 2012) and control of nuclear localisation (Shin and Reich, 2013). …”
Section: Discussionmentioning
confidence: 99%